A Systematic Review of Literature on Student Voice and Agency in Middle Grade Contexts - Mary Beth Schaefer; Sarah E. Pennington; Kent Divoll; Judy H. Tang (Education Sciences)
This systematic review analyzes the research literature on student voice and agency in the middle grades, focusing on middle-level schools, culture, and learning environments. The idea of student voice and agency was taken up as collaborative decision-making and/or student feedback on issues related to school and pedagogy. After a comprehensive search for peer-reviewed research (2015–2024), an article review framework was developed to determine how, where, and why student voices and agency were engaged in the middle grades. Three themes characterized the research literature: (1) passive student voice and agency: researcher-driven studies to gain understanding; (2) active student voice and agency: partnering with students to improve their learning experiences; and (3) activating the inner voice and agency: helping students to reflect on their own learning. The research on student voice and agency provided information that directly and indirectly benefited students. The literature related to passive student voice and agency tended to be indirect, while active student voice and agency and activating students’ inner voice and agency tended to provide tangible and observable student benefits. While the studies were responsive to different aspects of young adolescent development and included foci on students’ social/emotional development and identity, other areas were lacking—including culturally responsive teaching, international perspectives, and sense of self/peer perceptions.